Assessment of the Viability of a Biometric Characteristic in the Context of Biometric Authentication on Mobile Devices - Nawrocki, Piotr; Kubaty, Wojciech (Computing and Informatics, 2021)
The issue of safe utilization of mobile devices is becoming an increasingly important problem, among others due to the widespread use of such devices to access sensitive data (such as electronic documents or banking data). In our work we analyze the use of biometric techniques in order to secure a mobile device, with particular emphasis on the viability of selected biometric characteristics. For this purpose, we investigate the possibility of applying machine learning models to assess the authenticity of a biometric characteristic. Results of our tests have shown that the most effective method of assessing the viability of a biometric characteristic involves blink and smile detection.